New Insight into Quinoa Seed Quality under Salinity: Changes in Proteomic and Amino Acid Profiles, Phenolic Content, and Antioxidant Activity of Protein Extracts - Aloisi, Iris; Parrotta, Luigi; Ruiz, Karina B.; Landi, Claudia; Bini, Luca; Cai, Giampiero; Biondi, Stefania; Del Duca, Stefano (Frontiers in Plant Science, 2016)
Quinoa (Chenopodium quinoa Willd) is an ancient Andean seed-producing crop well known for its exceptional nutritional properties and resistance to adverse environmental conditions, such as salinity and drought. Storage proteins, amino acid composition, and bioactive compounds play a crucial role in determining the nutritional value of quinoa seeds. Seeds harvested from three Chilean landraces of quinoa, one belonging to the salares ecotype (R49) and two to the coastal-lowlands ecotype, VI-1 and Villarrica (VR), exposed to two levels of salinity (100 and 300 mM NaCl) were used to conduct a sequential extraction of storage proteins in order to obtain fractions enriched in albumins/globulins, 11S globulin and in prolamin-like proteins. The composition of the resulting protein fractions was analyzed by one- and two-dimensional polyacrylamide gel electrophoresis. Results confirmed a high polymorphism in seed storage proteins; the two most representative genotype-specific bands of the albumin/globulin fraction were the 30- and 32-kDa bands, while the 11S globulin showed genotype-specific polymorphism for the 40- and 42-kDa bands. Spot analysis by mass spectrometry followed by in silico analyses were conducted to identify the proteins whose expression changed most significantly in response to salinity in VR. Proteins belonging to several functional categories (i.e., stress protein, metabolism, and storage) were affected by salinity. Other nutritional and functional properties, namely amino acid profiles, total polyphenol (TPC) and flavonoid (TFC) contents, and antioxidant activity (AA) of protein extracts were also analyzed. With the exception of Ala and Met in R49, all amino acids derived from protein hydrolysis were diminished in seeds from salt-treated plants, especially in landrace VI-1. By contrast, several free amino acids were unchanged or increased by salinity in R49 as compared with VR and VI-1, suggesting a greater tolerance in the salares landrace. VR had the highest TPC and AA under non-saline conditions. Salinity increased TPC in all three landraces, with the strongest increase occurring in R49, and enhanced radical scavenging capacity in R49 and VR. Overall, results show that salinity deeply altered the seed proteome and amino acid profiles and, in general, increased the concentration of bioactive molecules and AA of protein extracts in a genotype-dependent